Quasi-static and impact behaviour of foam-filled graded auxetic panel - Novak, Nejc; Al-Rifaie, Hasan; Airoldi, Alessandro; Krstulović-Opara, Lovre; Łodygowski, Tomasz; Ren, Zoran; Vesenjak, Matej (International journal of impact engineering, 2023)
•The auxetic panels were built by corrugating and glueing aluminium sheets.•Detailed quasi-static and dynamic drop tests were conducted and compared with a non-linear computational model.•The stress-strain relationships, deformation patterns, specific energy absorption, crash force efficiency and Poisson's ratio were comprehensively evaluated.•The developed computational models successfully describe mechanical and deformation behaviour and can be used for future virtual testing of other configurations. Cellular structures (in general) and auxetic topologies (in particular) have excellent energy-dissipation characteristics and can be used as lightweight impact-energy absorbers. This paper aims to experimentally and computationally examine the behaviour of novel re-entrant auxetic graded aluminium panels filled with polyurethane foam in an auxetic pattern. The performance is compared with 3 non-graded, 1 graded and 2 foam-filled graded panels. The 6 compared auxetic panels share the same basic geometry but vary in the sheet thickness and the addition of polyurethane foam. The auxetic panels were built by corrugating and gluing 12 aluminium sheets. The material properties of the used aluminium sheets and foam were determined with standard mechanical testing. Detailed quasi-static and dynamic drop tests were conducted and compared with a non-linear computational model. The stress-strain relationships, deformation patterns, specific energy absorption, crash force efficiency and Poisson's ratio were comprehensively evaluated. Foam-filled panels revealed higher specific energy absorption and more stable deformation than non-filled panels. The developed computational models successfully describe mechanical and deformation behaviour and can be used for future virtual testing of other configurations.